Daytime Sleepiness from Preschool Children's and Parents' Perspectives: Is There a Difference? - Eugenija Marušić; Linda Lušić Kalcina; Ivana Pavlinac Dodig; Zoran Đogaš; Maja Valić; Renata Pecotić (MDPI AG, 2024)
This cross-sectional study investigated the level of daytime sleepiness and sleep-related behaviors in preschool children and compared their self-evaluations with the evaluations of their parents. It was conducted in Split-Dalmatian County, Croatia, among 196 preschool children aged 6-7 years seen at regular medical examinations, accompanied by their parents, using the Epworth sleepiness scale for children and parents/caregivers. Compared to their child's reports, parents tended to underestimate their child's sleepiness while sitting in a classroom at school (p = 0.001) and overestimate their child's sleepiness when lying down to rest or nap in the afternoon (p < 0.001). Boys were sleepier while sitting in a classroom at school during the morning than girls (p = 0.032). As much as 48.2% of preschool children had their own cellphones/tablets. Boys used video games (p < 0.001) and cellphones/tablets more than girls did (p = 0.064). Parental estimation of children playing video games at bedtime was lower than the child's report (p < 0.001). Children who had a TV in their bedroom reported more daytime sleepiness (p = 0.049), and those who played video games at bedtime went to sleep later during the weekend (p = 0.024). Also, children owning cellphone/tablets had longer sleep latency during the weekend compared to children not owning a cellphone (p = 0.015). This study confirmed that parents tend to underestimate children's habits of playing video games at bedtime and children's sleepiness during morning classes. Preschool children who use electronic devices at bedtime more frequently have prolonged sleep latency. These findings provide further evidence of the effects of electronic media devices on preschoolers' sleep patterns and daytime sleepiness.